Study of plant water lack message based on electric property and water potential of leaf - BAO Yi-dan; SHEN Jie-hui (浙江大学学报. 农业与生命科学版, 2005)
The relationship between the plant water lack degree and the electric property and water potential of leaf was studied with an aim of improving the measurement accuracy and speeding-up of information transfer. Leaf water potential of a plant fluctuated in the course of a day, which was dependent on change in weather conditions and was also controlled by certain intrinsic rules of physiology of the plant. Both measurement and comparison were complex. Fluctuation of leaf capacitance within a day was relatively inappreciable. The method described in this paper is quite easy and gives conspicuous result. It is just a new desirable method in obtaining the plant water lack degree quickly and exactly.